An unusual case of isolated unilateral palmar lichen nitidus - Shreya Singh; Kinjal Rambhia; Meena B Makhecha (Wolters Kluwer Medknow Publications, 2022)
Lichen nitidus (LN) is a benign chronic eruption characterized by numerous asymptomatic papules on the body, clustered at specific sites of predilection like the dorsum of hands, abdomen, and genitalia. A 10-year-old boy presented to us with asymptomatic roughness of the left palm for 2 years. Clinical examination revealed multiple discrete pin-point papules over the left palm. Histopathological examination revealed focal lichenoid granuloma with overlying parakeratosis suggestive of LN. Hence, we are reporting this case of LN which required histopathology for confirmation due to its atypical presentation and distribution.